Estimating clique size via discarding subgraphs - Szabo, Sandor; Zavalnij, Bogdan (Informatica, 2021)
The paper will present a method to establish an upper bound on the clique number of a given finite graph. In order to evaluate the proposed algorithm in practice we carry out a large scale numerical experiment.